Adenosine Diphosphate (ADP)-Induced ⍺-Granules Release from Platelets of Native Whole Blood Is Reduced by Ticlopidine but Not by Aspirin or Dipyridamole - Pengo, V; Boschello, M; Marzari, A; Baca, M; Schivazappa, L; Volta, S Dalla (Thrombosis and Haemostasis, 1986)
A brief contact between native whole blood and ADP promotes a dose-dependent release of platelet a-granules without a fall in the platelet number. We assessed the “ex vivo” effect of three widely used antiplatelet drugs, aspirin dipyridamole and ticlopidine, on this system. Aspirin (a single 800 mg dose) and dipyridamole (300 mg/die for four days) had no effect, while ticlopidine (500 mg/die for four days) significantly reduced the a-granules release for an ADP stimulation of 0.4 (p <0.02), 1.2 (p <0.01) and 2 pM (p <0.01). No drug, however, completeley inhibits this early stage of platelet activation. The platelet release of α-granules may be related to platelet shape change of the light transmission aggregometer and may be important “in vivo” by enhancing platelet adhesiveness and by liberating the plateletderived growth factor.
Keywords: Antiplatelet drugs; α-granules; β-TG; PF4